Penerapan Aplikasi Anates Untuk Analisis Soal HOTS Dalam Evaluasi Pembelajaran Spreadsheet Di SMKN 1 Kendal - Andrianik Susilowati, Dwi; Nidaria Saputri; Khafidhotun Ni’mah; Luqman Hakim; Vivi Pratiwi (CV. Ulil Albab Corp, 2025)
This study analyzes the quality of Higher Order Thinking Skills (HOTS)-based questions using the Anates application for class X Accounting students at SMKN 1 Kendal. The research involved 15 multiple-choice questions designed to assess students' analysis, evaluation, and synthesis skills, with data collected from 30 students. The analysis focused on reliability, difficulty level, discriminating power, distractor effectiveness, and validity. Results showed a reliability score of 0.76, indicating good consistency. However, only 3 out of 15 questions met validity criteria, while most had low correlations with total scores. The majority of questions were classified as very easy (>90%), failing to challenge critical thinking. Additionally, 80% of the questions had low discriminating power, and 60% of distractors were ineffective. These findings highlight the need for significant question revisions to align with HOTS standards. The Anates application proved useful in systematically identifying weaknesses and guiding improvements. This research aims to enhance the quality of evaluation instruments, particularly HOTS-based questions, in vocational high schools.